Cytotoxic and Antifungal Constituents Isolated from the Metabolites of Endophytic Fungus DO14 from Dendrobium officinale - Wu, Ling-Shang; Jia, Min; Chen, Ling; Zhu, Bo; Dong, Hong-Xiu; Si, Jin-Ping; Peng, Wei; Han, Ting (Molecules (Basel, Switzerland), 2016)
Two novel cytotoxic and antifungal constituents, (4S,6S)-6-[(1S,2R)-1, 2-dihydroxybutyl]-4-hydroxy-4-methoxytetrahydro-2H-pyran-2-one (1), (6S,2E)-6-hydroxy-3-methoxy-5-oxodec-2-enoic acid (2), together with three known compounds, LL-P880γ (3), LL-P880α (4), and Ergosta-5,7,22-trien-3b-ol (5) were isolated from the metabolites of endophytic fungi from Dendrobium officinale. The chemical structures were determined based on spectroscopic methods. All the isolated compounds 1–5 were evaluated by cytotoxicity and antifungal effects. Our present results indicated that compounds 1–4 showed notable anti-fungal activities (minimal inhibitory concentration (MIC) ≤ 50 μg/mL) for all the tested pathogens including Candida albicans, Cryptococcus neoformans, Trichophyton rubrum, Aspergillus fumigatus. In addition, compounds 1–4 possessed notable cytotoxcities against human cancer cell lines of HL-60 cells with the IC50 values of below 100 μM. Besides, compounds 1, 2, 4 and 5 showed strong cytotoxities on the LOVO cell line with the IC50 values were lower than 100 μM. In conclusion, our study suggested that endophytic fungi of D. officinale are great potential resources to discover novel agents for preventing or treating pathogens and tumors.